2018
DOI: 10.1264/jsme2.me17096
|View full text |Cite
|
Sign up to set email alerts
|

Host-Symbiont Cospeciation of Termite-Gut Cellulolytic Protists of the Genera <i>Teranympha</i> and <i>Eucomonympha</i> and their <i>Treponema</i> Endosymbionts

Abstract: Cellulolytic flagellated protists inhabit the hindgut of termites. They are unique and essential to termites and related wood-feeding cockroaches, enabling host feeding on cellulosic matter. Protists of two genera in the family Teranymphidae (phylum Parabasalia), Eucomonympha and Teranympha, are phylogenetically closely related and harbor intracellular endosymbiotic bacteria from the genus Treponema. In order to obtain a clearer understanding of the evolutionary history of this triplex symbiotic relationship, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…The gut of R. speratus termites contains another symbiotic flagellate, namely Teranympha mirabilis (Koidzumi, 1921;Noda et al, 2018), which we found also to harbor numerous centrioles and associated flagella ( Fig. S8A).…”
Section: Diversity Of Cartwheel Architecture In Teranympha Cartwheelmentioning
confidence: 89%
“…The gut of R. speratus termites contains another symbiotic flagellate, namely Teranympha mirabilis (Koidzumi, 1921;Noda et al, 2018), which we found also to harbor numerous centrioles and associated flagella ( Fig. S8A).…”
Section: Diversity Of Cartwheel Architecture In Teranympha Cartwheelmentioning
confidence: 89%
“…Common but numerically poorly represented microbiota members belong to genera Treponema, Fusobacterium, Akkermansia, Mucispirillum, Elusimicrobium or Cloacibacillus, each of them belonging to a different phylum such as Spirochaetes, Fusobacteria, Verrucomicrobia, Defferibacteres, Elusimicrobia and Synergistetes, respectively. Treponema species are likely involved in fibre digestion as this is their function in termite microbiota [47] and enrichment for Treponema has been described also in humans from rural areas [48,49]. Treponema species are also more common in pigs [50,51], whose feed formula is rich in plant fibre.…”
Section: Other Bacteria Colonising the Chicken Intestinal Tractmentioning
confidence: 99%
“…In co-cultures of T. primitia and H 2 -producing Treponema azotonutricium, interspecies transfer of H 2 was demonstrated [80]. In 'Candidatus Treponema intracellularis' and 'Candidatus Treponema teratonymphae', which are intracellular symbionts of parabasalid protists, it has been hypothesised that these endosymbiotic H 2 /CO 2 -homoacetogens decrease the high H 2 partial pressure inside their protist hosts, thereby promoting the fermentation process of host cells [65,81]. However, to the best of our knowledge, the attachment of an H 2 -producing bacterium to an H 2 /CO 2 -homoacetogenic spirochete has hitherto never been reported.…”
Section: Discussionmentioning
confidence: 99%